Profile of inmates of a special school for the mentally ill and disabled in Kancheepuram district, Tamil Nadu: An institution based cross-sectional study - Saurabh RamBihariLal Shrivastava; Prateek S Shrivastava; Jegadeesh Ramasamy (Wolters Kluwer Medknow Publications, 2015)
Context : The health care and social welfare needs of persons with mental illness and differently abled persons should not be ignored. Aim: The aim of the study is to assess the socio-demographic and morbidity profiles of the inmates in the special school and to explore the reasons that have contributed to their admission in the school. Materials and Methods: A cross-sectional descriptive study of six months duration (September 2013 to February 2014) was conducted in a special school for mentally ill and differently abled people of Kanchipuram district in Tamilnadu. All the inmates staying in the school during the study period were included as study participants. The socio-demographic profile of the inmates was obtained with the help of caretaker/family members/records maintained by the center while their morbidity profile was explored with the help of specialists from different departments. Statistical analysis was done using SPSS version 18 and the frequency distributions and percentages were calculated for all the variables. Results: Most of the study participants, 31 (56.4%) were from the 40-60 years age group. Overall, 51 (92.7%) inmates were suffering from some type of mental disorders with/without multiple disabilities while 4 (7.2%) inmates were enrolled in the special school because of their old age. The unwillingness of the family members to take care of the affected person was cited as the most common cause in 32 (58.1%) of the inmates for enrolling in the special school. Conclusion: Most of the inmates of the special school were suffering from mental illnesses with/without multiple disabilities. A definite improvement in the quality of life of inmates has been observed after the extension of healthcare services by the medical college.